2022
DOI: 10.3389/fonc.2021.823054
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Prognostic Nutritional Index and Neutrophil-to-Lymphocyte Ratio Predict Survival Outcomes of Patients With Hepatocellular Carcinoma After Curative Resection

Abstract: Increasing evidence indicates that preoperative prognostic indices can serve as independent predictors of survival in patients with cancer. However, the applicability of these indices in patients with hepatocellular carcinoma (HCC) is controversial. This study aims to investigate the prognostic value of these indices in patients with HCC after curative hepatectomy. We retrospectively analyzed the data of 215 patients who underwent curative resection for HCC. Prognostic indices including prognostic nutritional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Nomograms have been widely used as a visual tool to predict the survival of HCC patients. Two studies combined NLR with other noninflammatory indicators to construct a nomogram, providing personalized prediction of survival for HCC patients after curative resection [24,25]. Yu et al [26] constructed a comprehensive nomogram based on SII and emphasized that SII was an independent prognostic factor affecting the survival outcome of HCC patients after radiofrequency ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Nomograms have been widely used as a visual tool to predict the survival of HCC patients. Two studies combined NLR with other noninflammatory indicators to construct a nomogram, providing personalized prediction of survival for HCC patients after curative resection [24,25]. Yu et al [26] constructed a comprehensive nomogram based on SII and emphasized that SII was an independent prognostic factor affecting the survival outcome of HCC patients after radiofrequency ablation.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the quality of the included trials, basic data were extracted, as shown in Table 1 . Of the 16 trials, 15 were in East Asia and the remaining 1 was in West Africa ( 43 ), including 11 in mainland China ( 34 , 37 , 39 41 , 44 , 46 50 ), 1 in South Korea ( 38 ), 2 in Taiwan ( 33 , 51 ), and 1 in Japan ( 36 ). All studies are from single-center clinical trials between 2012 and 2022.…”
Section: Resultsmentioning
confidence: 99%
“…Systemic inflammation and nutritional disorders promote cell carcinogenesis by inhibiting apoptosis, promoting angiogenesis, and damaging DNA. The PNI, an indicator of nutritional status and systemic immune capacity, has been shown to be an independent prognostic factor for a variety of cancers [ 38 ]. Previous studies have shown that PNI is significantly correlated with tumor infiltrating lymphocyte status, the density of CD4 + and CD8 + immune cells, and systemic inflammation [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%